Implementation of The Policy for The Appointment of Prospective Government Employees with Work Agreements In Minahasa Regency - Lababa, Sri Wahyuni; Langkai, Jeane E.; Dilapanga, Abdul Rahman (Technium Social Sciences Journal, 2024)
This research aims to evaluate the policy for appointing honorary teachers as candidates for Government Employees with Work Agreements (PPPK) in Minahasa Regency. The approach used in this research is a qualitative method. Data was obtained through interviews, observations, and documentation carried out at the Minahasa Regency Human Resources Development Personnel Agency and the Minahasa Regency Education Office. The results of the research show that the process of appointing honorary workers to become candidates for Government Employees with Work Agreements in Minahasa Regency has gone well and is in accordance with the criteria set by the researchers. The determinant factors of this process involve identifying vacant positions, searching for job information through job analysis, selecting suitable candidates, choosing the most appropriate recruitment method, selecting candidates who meet the job requirements, screening candidates, making job offers, and finally starting work.